2001
DOI: 10.1083/jcb.200107045
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of Golgi structure and function depends on the integrity of ER export

Abstract: The Golgi apparatus comprises an enormous array of components that generate its unique architecture and function within cells. Here, we use quantitative fluorescence imaging techniques and ultrastructural analysis to address whether the Golgi apparatus is a steady-state or a stable organelle. We found that all classes of Golgi components are dynamically associated with this organelle, contrary to the prediction of the stable organelle model. Enzymes and recycling components are continuously exiting and reenter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

55
485
2
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 385 publications
(543 citation statements)
references
References 55 publications
55
485
2
1
Order By: Relevance
“…In HeLa cells, Bap31 cycled between the juxtanuclear and peripheral regions more slowly compared with COS-7 cells; the ratio of HeLa cells with juxtanuclear Bap31 accumulation to total cells was maximum at 120 min after BFA washout (Supplemental Figure S5). As shown previously (Nakamura et al, 1995;Ward et al, 2001) and in this study ( Figure 1E), BFA treatment caused some dispersion of ERGIC-53-positive clusters at the juxtanuclear region without changing punctate ERGIC-53 staining at the peripheral region. When BFA was washed out, ERGIC-53 seemed to become concentrated at the juxtanuclear region (Supplemental Figure S6).…”
supporting
confidence: 90%
See 2 more Smart Citations
“…In HeLa cells, Bap31 cycled between the juxtanuclear and peripheral regions more slowly compared with COS-7 cells; the ratio of HeLa cells with juxtanuclear Bap31 accumulation to total cells was maximum at 120 min after BFA washout (Supplemental Figure S5). As shown previously (Nakamura et al, 1995;Ward et al, 2001) and in this study ( Figure 1E), BFA treatment caused some dispersion of ERGIC-53-positive clusters at the juxtanuclear region without changing punctate ERGIC-53 staining at the peripheral region. When BFA was washed out, ERGIC-53 seemed to become concentrated at the juxtanuclear region (Supplemental Figure S6).…”
supporting
confidence: 90%
“…GM130 is one of the fast-moving proteins during BFA recovery (Jiang et al, 2006). As reported previously (Nakamura et al, 1995;Seemann et al, 2000;Ward et al, 2001), GM130 was distributed in punctate structures in BFA-treated cells (Supplemental Figure S3, second row). Although previous studies showed that combined treatment of normal rat kidney or HeLa cells with BFA followed by BFA plus H89 causes ER localization of GM130 (Puri and Linstedt, 2003;Jiang et al, 2006), such redistribution was not observed in COS-7 cells when 50 M H89 in addition to 10 M BFA was used (data not shown).…”
Section: Bap31 Movement and Golgi Reassembly Occur Independently Durisupporting
confidence: 80%
See 1 more Smart Citation
“…LIS1 was previously shown to be involved in the dynein motor complex that determines microtubule-associated movement of organelles and membrane vesicles [18][19][20][21][22][23][24][25][26] and maintenance of the integrity of the Golgi apparatus and juxta-centrosomal distribution of its membranes (reviewed in refs. [27][28][29][30][31][32][33][34][35]. The comparison of the effects of 3A and dominant negative mutants of LIS1, which inhibit surface receptor recovery, suggests that 3A acts by trapping LIS1-containing complexes on the cytoplasmic surface of the ER, thereby preventing it from transporting proteins between the ER and the Golgi.…”
Section: Introductionmentioning
confidence: 99%
“…This might help explain the variability in the amount of Golgi haze that is seen in different cell types. The status of the matrix is, however, still unclear, and its existence has been disputed (Zaal et al, 1999;Miles et al, 2001;Ward et al, 2001;Stroud et al, 2003). In the merged ER-Golgi model of partitioning, the MGCs are viewed as intermediates on the pathway leading to merger of the Golgi and the ER.…”
mentioning
confidence: 99%